The complete mitochondrial genome of a vulnerable cyprinid fish Onychostoma macrolepis (Teleostei: Cypriniformes) from Qinling-Bashan Mountain area in China. Issue 2 (2nd April 2020) - Chen, Suwei; Tang, Qiongying
Abstract: A cyprinid fish Onychostoma macrolepis is endemic to China with high economic values, and its natural resource is decreasing dramatically in recent years. In this study, the complete mitogenome sequence of O. macrolepis from Qinling-Bashan Mountain area was determined using next-generation sequencing. The mitogenome is 16, 597 bp in length, including 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and one non-coding control region with 940 bp in length. The phylogenetic analyses based on whole mitogenome sequences indicated that the genus Onychostoma did not form monophyly, and it was divided into two clades. The present result will provide basic data for the genetic diversity conservation of O. macrolepis.